Indoor noise A-level assessment related to the environmental noise spectrum on the building facade. (1st January 2022) - Zaporozhets, Oleksandr; Fiks, Boris; Jagniatinskis, Aleksandras; Tokarev, Vadim; Karpenko, Serhii; Mickaitis, Marius
Abstract: There is a growing body of research reporting that unwanted indoor noise can negatively affect the well-being of the occupants. According to the World Health Organisation (WHO), indoor guideline values in dwellings are 30 dBA (LAeq, night, indoor ), which in turn should also include appropriate airborne and impact sound insulation of façades. Such low noise values in dwellings are difficult to measure, which is why indirect methods of indoor noise assessment (including the accurate calculation and measurement procedures for sound insulation of dwelling façades) are an important issue worth investigating. Therefore, in this paper, a new methodology of how indoor noise A-level may be assessed by applying the outdoor noise monitoring and standardized sound insulation measurement of the façade is proposed. It also provides an overview of the existing difficulties in performing accurate calculations of the sound insulation on the façades. The proposed calculation procedure for indoor equivalent noise A-level estimation is also evaluated. The highest accuracy was achieved by adding to the calculation a specific spectrum adaptation term Cspec, 100-3150 for the noise emitted façade in-situ instead of a standard spectrum adaptation term Ctr, 100-3150, defined by the unified spectra corresponding to road traffic, and suggested by the ISO 717–1 for the calculations. The specific spectrum adaptation term was calculated based on the averaged spectrum of the specific noise events (different from road traffic noise) that contribute to the outdoor environment at the locations where measurements were carried out. When assessed in such a way, the equivalent sound levels of indoor noise, which are produced by different types of outdoor noise sources, show a good agreement with the directly measured levels indoors.